Midnight's Children - Salman Rushdie (Atlantic Books, 2013)
Born at the stroke of midnight at the exact moment of India's independence, Saleem Sinai is a special child. However, this coincidence of birth has consequences he is not prepared for: telepathic powers connect him with 1,000 other \\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\'midnight\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\'s children\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\' all of whom are endowed with unusual gifts. Inextricably linked to his nation, Saleem\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\'s story is a whirlwind of disasters and triumphs that mirrors the course of modern India at its most impossible and glorious. - See more at: http://www.easons.com/p-776504-midnights-children.aspx#sthash.2hMmNxIh.dpuf